Transforming agriculture: advancements in compost-biopolymers composites for enhanced sustainability (2024)
In the Cesar Department in Colombia, sustainable agriculture faces critical challenges despite its thriving livestock sector. Extensive cattle ranching and poor soil management worsen soil conditions. Additionally, significant environmental concerns arise from the substantial discharge of wastewater in the dairy processing industry. This study aims to valorize biosolids derived from wastewater during dairy plant disinfection to enhance sustainable livestock production. It explores the use of biosolids as the primary matrix for creating composted compounds and biopolymers for agricultural purposes. These composite materials utilize composted biosolids from the dairy industry as the main matrix (60%), blended with biodegradable polymers such as polybutylene adipate succinate (PBSA) and polylactic acid (PLA) as functional agents. This innovative approach contrasts with the prevailing literature on composite polymer materials, where polymers typically form the matrix and agricultural residues serve as fillers. Biosolids from Freskaleche S.A. undergo controlled thermal treatment and composting before being combined with PBSA and PLA polymers using an internal mixer. The development of these new compounds includes the evaluation of thermal stability, Fourier-transform infrared spectroscopy (FTIR), and mechanical properties. It is noteworthy that Compost/PBSA composites exhibit promising compatibility and thermomechanical properties resembling pure PBSA, suggesting their potential as thermoplastic materials for producing plastic-based agricultural products. Regarding Compost/PLA blends, compost enhances chemical reactions in PLA polymeric chains, significantly altering their thermomechanical properties. This research provides valuable insights into the use of biosolids for manufacturing composite materials, offering a sustainable approach to address agricultural challenges in the Cesar region.